Independence of young people with cerebral palsy during transition to adulthood: a population-based 3 year follow-up study - Jahnsen Reidun; Ramstad Kjersti; Myklebust Gerd; Elkjaer Sonja; Pripp Are Hugo; Klevberg Gunvor Lilleholt (De Gruyter, 2020)
This study describes developmental and service transitions during a 3-year period among young people with cerebral palsy (CP) as measured by the Rotterdam Transition Profile (RTP) and evaluates the test-retest reliability of the RTP. The RTP is a questionnaire developed to classify phases of transition across nine participation domains.